Autophagy: A New Avenue and Biochemical Mechanisms to Mitigate the Climate Change - Muhammad Abubakkar Azmat; Malaika Zaheer; Muhammad Shaban; Saman Arshad; Muhammad Hasan; Alyan Ashraf; Muhammad Naeem; Aftab Ahmad; Nayla Munawar (Scientifica)
Autophagy is a preserved process in eukaryotes that allows large material degeneration and nutrient recovery via vacuoles or lysosomes in cytoplasm. Autophagy starts from the moment of induction during the formation of a phagophore. Degradation may occur in the autophagosomes even without fusion with lysosome or vacuole, particularly in microautophagosomes. This process is arbitrated by the conserved machinery of basic autophagy-related genes (ATGs). In selective autophagy, specific materials are recruited by autophagosomes via receptors. Selective autophagy targets a vast variety of cellular components for degradation, i.e., old or damaged organelles, aggregates, and inactive or misfolded proteins. In optimal conditions, autophagy in plants ensures cellular homeostasis, proper plant growth, and fitness. Moreover, autophagy is essential during stress responses in plants and aids in survival of plants. Several biotic and abiotic stresses, i.e., pathogen infection, nutrient deficiency, plant senescence, heat stress, drought, osmotic stress, and hypoxia induce autophagy in plants. Cell death is not a stress, which induces autophagy but in contrast, sometimes it is a consequence of autophagy. In this way, autophagy plays a vital role in plant survival during harsh environmental conditions by maintaining nutrient concentration through elimination of useless cellular components. This review discussed the recent advances regarding regulatory functions of autophagy under normal and stressful conditions in plants and suggests future prospects in mitigating climate change. Autophagy in plants offers a viable way to increase plant resilience to climate change by increasing stress tolerance and nutrient usage efficiency.